Bài 7:
a)
\(A=x\left(2x+1\right)-x^2\left(x+2\right)+x^3-x+3\\ =2x^2+x-x^3-2x^2+x^3-x+3\\ =\left(2x^2-2x^2\right)+\left(x-x\right)+\left(-x^3+x^3\right)+3\\ =3\)
Vậy ..........
b)
\(B=2x\left(x-1\right)-x\left(2x+1\right)-\left(3-3x\right)\\ =2x^2-2x-2x^2-x-3+3x\\ =\left(2x^2-2x\right)+\left(-2x-x+3x\right)-3\\ =-3\)
Vậy ...........
c)
\(C=\left(2x+11\right)\left(3x-5\right)-\left(2x+3\right)\left(3x+7\right)\\ =6x^2-10x+33x-55-\left(6x^2+14x+9x+21\right)\\ =6x^2-10x+33x-55-6x^2-14x-9x-21\\ =\left(6x^2-6x^2\right)+\left(-10x+33x-14x-9x\right)-55-21\\ =-76\)
Vậy .............
d)
\(D=x\left(2x^2-4x+8\right)+12x^2\left(\dfrac{1}{3}-\dfrac{1}{6}x\right)-8x+9\\ =2x^3-4x^2+8x+4x^2-2x^3-8x+9\\ =\left(2x^3-2x^3\right)+\left(-4x^2+4x^2\right)+\left(8x-8x\right)+9\\ =9\)
Vậy ...............
`HaNa♬D`
Bài 7.
\(a,A=x\left(2x+1\right)-x^2\left(x+2\right)+x^3-x+3\)
\(=2x^2+x-x^3-2x^2+x^3-x+3\)
\(=\left(-x^3+x^3\right)+\left(2x^2-2x^2\right)+\left(x-x\right)+3\)
\(=3\)
⇒ Giá trị của A không phụ thuộc vào giá trị của biến
\(b,B=2x\left(x-1\right)-x\left(2x+1\right)-\left(3-3x\right)\)
\(=2x^2-2x-2x^2-x-3+3x\)
\(=\left(2x^2-2x^2\right)+\left(-2x-x+3x\right)-3\)
\(=-3\)
⇒ Giá trị của B không phụ thuộc vào giá trị của biến
\(c,C=\left(2x+11\right)\left(3x-5\right)-\left(2x+3\right)\left(3x+7\right)\)
\(=6x^2-10x+33x-55-\left(6x^2+14x+9x+21\right)\)
\(=6x^2+23x-55-6x^2-23x-21\)
\(=\left(6x^2-6x^2\right)+\left(23x-23x\right)+\left(-55-21\right)\)
\(=-76\)
⇒ Giá trị của C không phụ thuộc vào giá trị của biến
\(d,D=x\left(2x^2-4x+8\right)+12x^2\left(\dfrac{1}{3}-\dfrac{1}{6}x\right)-8x+9\)
\(=2x^3-4x^2+8x+4x^2-2x^3-8x+9\)
\(=\left(2x^3-2x^3\right) +\left(-4x^2+4x^2\right)+\left(8x-8x\right)+9\)
\(=9\)
⇒ Giá trị của D không phụ thuộc vào giá trị của biến
#Urushi
Bài 8.
\(a,A=2x\left(\dfrac{1}{2}x^2+y\right)-x\left(x^2+y\right)+xy\left(x^3-1\right)\)
\(=x^3+2xy-x^3-xy+x^4y-xy\)
\(=\left(x^3-x^3\right)+\left(2xy-xy-xy\right)+x^4y\)
\(=x^4y\)
Thay \(x=10;y=-\dfrac{1}{10}\) vào A, ta được:
\(A=10^4\cdot\left(-\dfrac{1}{10}\right)\)
\(=-\dfrac{10^4}{10}\)
\(=-10^3\)
\(=-1000\)
Vậy \(A=-1000\) tại \(x=10;y=-\dfrac{1}{10}\)
\(b,B=3x^2\left(x^2-5\right)+x\left(-3x^3+4x\right)+6x^2\)
\(=3x^4-15x^2-3x^4+4x^2+6x^2\)
\(=\left(3x^4-3x^4\right)+\left(-15x^2+4x^2+6x^2\right)\)
\(=-5x^2\)
Thay \(x=-5\) vào B, ta được:
\(B=-5\cdot\left(-5\right)^2\)
\(=\left(-5\right)^3\)
\(=-125\)
Vậy \(B=-125\) tại \(x=-5\).
#Urushi